Effects of rumen fluid transplantation on the fecal flora of yaks - Zhang, Man; Li, Yan; Li, Yumin; Cheng, Chenxu; Chai, Shatuo; Yang, Yingkui; Wang, Xun; Wang, Shuxiang (Frontiers in Animal Science, 2025)
IntroductionThere are few studies on the effect of rumen fluid transplantation on the fecal flora of yaks. Yak fecal flora is closely related to their health. This study aimed to evaluate the effects of rumen fluid transplantation on growth performance and fecal flora indicators.MethodsTwenty 6-month healthy male yaks (weight: 57.20 ± 7.80 kg) were selected from grazing yaks in an alpine meadow pasture at an altitude of approximately 3,400 m. They were then transferred to a farm and randomly divided into a control group (CON; n = 10) and a rumen fluid transplantation group (RT; n = 10). Separate single-pen rearing was performed in two pens using the same rearing environment and feeding method, and all yaks were earmarked for identification. In addition, 10 yaks that had been adapted to stall fattening feed in 1 month were selected as the rumen fluid donor group to provide fresh rumen fluid. Ruminal fluid transplantation trials were conducted on the 1st, 3rd, and 5th weeks. Overall, 1 L of ruminal fluid was transplanted to each yak in the RT and CON groups. The formal trial then began with both groups fed the same diet. After this, yak feed intake was recorded daily; yaks were weighed on days 1, 30, and 60 of the formal trial; and yak feces were collected directly from the ground on days 1, 4, 7, 14, 30, and 60 to compare the microbial composition of the feces using 16S rRNA sequencing data.ResultsThe results showed that rumen fluid transplantation significantly increased the alpha diversity of fecal microflora (P < 0.05), and on day 30 of the experiment, both the operational taxonomic unit (OTU) and Shannon index were significantly higher in the RT group than the CON group (P < 0.05). In the principal coordinate analysis (PCoA) plot, the intestinal flora of the RT group was significantly different (P < 0.05) on days 1–7 but not significantly different after day 14. In contrast, the intestinal flora of the CON group was significantly different (P < 0.05) on days 1–14 but not significantly different after day 30. Compared with the CON group, the relative abundance of Firmicutes in the RT group was significantly lower on days 1, 4, 7, and 14 (P < 0.05); the relative abundance of Bacteroidetes in the RT group was significantly higher on days 1, 4, 14, and 30 and significantly lower on day 7 (P < 0.05); the relative abundance of Tenericutes in the RT group was significantly higher on day 30 (P < 0.05); the relative abundance of Actinobacteria in the RT group was significantly higher on day 60 (P < 0.05); the relative abundance of Ruminococcaceae_UCG-005 in the RT group was significantly lower on days 4, 7, 14, and 60 (P < 0.05); the relative abundance of Unidentified in the RT group was significantly higher on days 1, 4, and 7 days (P < 0.05); and the relative abundance of Rikenellaceae_RC9_gut_group, Bacteroides, and Christensenellaceae_R-7_group in the RT group was significantly higher on day 1 (P < 0.05). Moreover, Actinobacteria was positively correlated with ADG and negatively correlated with DMI; Tenericutes was positively correlated with weight and negatively correlated with F/G. Metabolism of terpenes and polyketones, metabolism of other amino acids, and energy metabolism were higher in the RT group than in the CON group. LEfSe analysis showed that 32 species were more abundant in the RT group and 11 in the CON group. In conclusion, our findings suggest that rumen fluid transplantation improved the stability of the intestinal tract of yaks, improved the immunity of yaks, and reduced the occurrence of intestinal diseases; rumen fluid transplantation remodeled the structure of the intestinal flora, shortened the time of remodeling the intestinal flora of yaks during the transition period, and accelerated yak adaptation to digest housed rations, reducing the DMI. The findings of this study provide new insights into yak microbial community transplantation and a reference for improving feed efficiency in the yak industry.